To fear or not to fear? – The effect of early posterior negativity on reaction times in response to threatening animal stimuli - Kraufvelin, Nelli (My University, 2023)
The snake detection theory (SDT) proposes snakes to have been the most important factor driving the evolution of the visually specialized, expanded brains of primates. Evidence from many studies has supported this idea, as it has been found that people are faster at detecting snakes among innocuous stimuli than they are at detecting innocuous stimuli in matrices of snakes or other threatening stimuli. In addition, electroencephalography (EEG) studies measuring electric potentials of the brain have found differential processing of snake pictures compared to other (innocuous and non-innocuous) animal stimuli, as they elicit particularly strong negative-going activity in the posterior channels at around 200-300ms after stimulus onset. This component called early posterior negativity (EPN) is known to be especially modulated by emotionally arousing stimuli. Faster reaction times to snakes as well as the EPN snake effect have been interpreted as evidence for the snake detection theory, yet no studies to date seem to have examined the possible correlation between the two. This study was conducted to investigate the matter. To increase the ecological validity to the results, a naturalistic paradigm was used. In this paradigm, participants reacted to snakes by standing in front of a large touch screen monitor, placing their finger on the screen before each trial. If an experimental stimulus was shown, the participants had to withdraw their arm away from the screen as fast as they could. Reaction times were measured both by simple reaction times measured from the moment that the participant’s finger was removed from the screen, as well as acceleration, which was measured with an accelerometer that was attached to the participant’s wrist. For the analyses, peak acceleration, which was calculated from the accelerometer data, was used. EEG was recorded throughout the experiment. As expected, snakes were found to elicit stronger EPN amplitudes compared to other animal stimuli. Moreover, a negative correlation between mean EEG amplitude at 200-300ms after stimulus onset, and reaction times, was found, meaning that stronger EPN was correlated with slower reaction times. This was opposite to what was expected, as faster reaction times as well as larger EPNs have both previously been associated with snakes. These surprising results suggest that the relationship between the EPN and reaction times is not as simple as assumed. It seems that the EPN is caused and modulated by a more complicated cognitive process than previously thought. The results from this study provide interesting and new insights into the EPN and its role in snake detection and otherwise. More research is needed to further these insights and provide even better understanding of this event-related component.
Keywords: early posterior negativity, snake detection theory, mammalian fear module, EEG, ERP